2021
DOI: 10.1155/2021/1025669
|View full text |Cite|
|
Sign up to set email alerts
|

Financial Development and Carbon Emissions: Analyzing the Role of Financial Risk, Renewable Energy Electricity, and Human Capital for China

Abstract: This study introduces the role of financial risk index and renewable energy electricity output along with financial development and human capital as new determinants of carbon emissions and uses updated time-series data from 1988–2018 for China, employing novel econometric approaches, i.e., Narayan and Popp unit root test with structural breaks, Maki cointegration, and frequency domain causality test for long, short, and medium run causality. The empirical outcome shows that improvement in human capital index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Similar findings can be found in Zhang M. et al (2022), and Zheng and Ge (2022). Many scholars support this view and argue that China's achievement of carbon peak and carbon neutrality depends on RBC's low-carbon development (Ma et al, 2021;Guo, 2021;Liao et al, 2022). According to statistics, RBCs consume 60% of national energy (Fong et al, 2008;Zhang H. et al, 2022).…”
Section: Introductionsupporting
confidence: 56%
“…Similar findings can be found in Zhang M. et al (2022), and Zheng and Ge (2022). Many scholars support this view and argue that China's achievement of carbon peak and carbon neutrality depends on RBC's low-carbon development (Ma et al, 2021;Guo, 2021;Liao et al, 2022). According to statistics, RBCs consume 60% of national energy (Fong et al, 2008;Zhang H. et al, 2022).…”
Section: Introductionsupporting
confidence: 56%
“…For instance, Tamazian et al (2009) for Brazil, Russia, India, and China, Islam et al (2013) for Malaysia, Lee et al (2015) for 25 OECD nations, Saidi and Mbarek (2017) for nineteen emerging nations, Zaidi et al (2019) for a set of countries, and Guo (2021) for China found that financial development reduces environmental contamination.…”
Section: Financial Development and Environmental Deteriorationmentioning
confidence: 99%
“…The findings indicate that the FR indices have a monotonically rising impact on CO 2 emissions and, consequently lower EQ across the whole sample. Using revised time‐series data for China between 1988 and 2018, Guo (2021) looks at the role of financial risk as a new driver of CO 2 . The author employs unique econometric methodologies such as the frequency domain causality test and Maki cointegration.…”
Section: Literature Reviewmentioning
confidence: 99%